Some pharmacogenetic aspects of the ABCB1 gene in lopinavir / ritonavir concentration variability in children with HIV infection: A pilot study - A. Yu. Sambyalova; T. A. Bairova; T. L. Manaenkova; A. V. Belskikh; E. V. Belyaeva; O. A. Ershova; D. V. Kumratov; A. I. Paramonov; Yu. K. Plotnikova; L. V. Kolomeets; L. V. Rychkova (Acta Biomedica Scientifica)
Polymorphic variants of the multidrug resistance gene (ABCB1 or MDR1) are associated with changes in the absorption and transport of drugs in the body. One of the substrates of the ABCB1 transporter is an antiretroviral drug from the class of protease inhibitors, lopinavir.   The aim. To research the effect of polymorphic variants C1236T and C3435T in the ABCB1 gene on the plasma concentration of lopinavir / ritonavir in children and adolescents living with HIV infection.   Methods. The genotypes of polymorphic variants of the ABCB1 gene were identified in 136 HIV infected children and adolescents; median age – 10 [7–12] years. The plasma concentration of lopinavir / ritonavir was measured from blood taken during the next scheduled appointment as part of dispensary observation at the Irkutsk Regional AIDS Centre using high performance liquid chromatography.   Results. The average duration of lopinavir/ritonavir use as part of an antiretroviral therapy was 55 months. Median viral load in patients was 1 [1–2.03] log 10  copies/ mL; the number of CD4 +  T cells – 38.36 %. The frequency of occurrence of the 3435T and 1236T alleles of the ABCB1 gene was ~50 %. In carriers of the 3435TT genotype, the median lopinavir concentrations 2 and 12 hours after drug intake were 5050.8 [3615.8–5847.7] and 2665.5 [216–4896.3] ng/mL, respectively. In carriers of the 1236TT genotype, median lopinavir concentrations 2 and 12 hours after drug intake were 4913.5 [3355.1–5733.7] and 3290.6 [159.1–4972.5] ng/mL, respectively.   Conclusions. The study did not reveal a significant relationship between the carriage of the C3435T and C1236T genotypes of the ABCB1 gene and the concentrations of lopinavir and ritonavir 2 and 12 hours after drug intake.